2013
DOI: 10.1002/pssa.201228751
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment and substrate dependant properties of titania thin films with high copper loading

Abstract: Copper-doped titania thin films have been prepared on SiO 2 / Si(100), fused-silica and soda-lime glass substrates by using sol-gel deposition and subsequent annealing in air atmosphere at 200-900 8C. Several experimental techniques [X-ray photoelectron spectroscopy (XPS), wavelength dispersive X-ray fluorescence (WDXRF), Raman spectroscopy, atomic force microscopy (AFM), UV-Vis spectroscopy, energy dispersive X-ray analysis (EDX), photocatalytic activity measurements and hydrophilicity measurements] have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…Raman spectra of pure and doped TiO 2 films (Figure ) show a sharp peak at 143 cm −1 ( E g (1)), a weak peak at 197 cm −1 ( E g (2)), and three medium intensity peaks at 397 cm −1 ( B 1g (1)), 516 cm −1 ( A 1g + B 1g (2)), and 638 cm −1 ( E g (3)) which are characteristic of the anatase phase. These values are in agreement with those reported by Joost et al The anatase phase was also observed in the XRD data, shown above. The intense low frequency peak at 143 cm −1 is due to O–Ti–O bending vibrations .…”
Section: Resultssupporting
confidence: 93%
“…Raman spectra of pure and doped TiO 2 films (Figure ) show a sharp peak at 143 cm −1 ( E g (1)), a weak peak at 197 cm −1 ( E g (2)), and three medium intensity peaks at 397 cm −1 ( B 1g (1)), 516 cm −1 ( A 1g + B 1g (2)), and 638 cm −1 ( E g (3)) which are characteristic of the anatase phase. These values are in agreement with those reported by Joost et al The anatase phase was also observed in the XRD data, shown above. The intense low frequency peak at 143 cm −1 is due to O–Ti–O bending vibrations .…”
Section: Resultssupporting
confidence: 93%
“…A significant decrease in film thickness is observed with the addition of copper. This is probably due to the increase in crystallinity and grain size of the film, as can be also seen from the XRD and AFM results [25,26].…”
Section: Tablesupporting
confidence: 53%
“…Pure TiO 2 and Copper-Titanium oxide thin films are deposited on clean glass substrates by sol-gel dip coating method using titanium tetraisopropoxide and copper (II) acetate as starting precursors. The amount of Cu in the solution is adjusted to be 0, 12.5 wt%, 25 4 , Merck] is incorporated into the solution. In the final step, 1 ml trietilamine [(C 2 H 5 ) 3 N, Merck] is incorporated into the solution and the final solution is mixed for 2 h on the magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
“…Antibacterial applications of TiO 2 often use thin film coatings that can be deposited by various methods including sputtering [17], chemical solution deposition [18], pulsed laser deposition [19] or sol-gel method [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%